PERANAN BALAI PEMASYARAKATAN DALAM SISTEM PERADILAN PIDANA ANAK DITINGKAT PENUNTUTAN DAN PUTUSAN DI PENGADILAN NEGERI BANGKINANG - Setiawan, M. Arie; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In law number 11 of 2012 about the Child Criminal Justice System gives a role to the community officer. Community Officer is a Community Care Counselor who works at the Correctional Office. The purpose of this thesis is to know the role of Correctional Office in the child criminal justice system at the level of prosecution and verdict in Bangkinang District Court.This type of research can be classified with the type of sociological juridical research, because in this study the authors conducted directly the research on the location or place which studied in order to provide a complete and clear picture of the problem under study. This research was conducted in the jurisdiction of the Bangkinang District Court, while the population and the sample were the whole parties which related to the problem studied in this study. Sources of data used, primary data, secondary data and tertiary data, data collection techniques in this study by interview and literature study.From the results of research that has been done by the authors can be concluded. First, The Child Prosecutor is not necessarily guided completely by the Community Research Report that created by the Post of Correctional Office Correctional Institution Class IIB Bangkinang. Second, The Judge of Child is not necessarily guided completely to the Community Research Report that created by by the Post of Correctional Office Correctional Institution Class IIB Bangkinang.Keywords: Prosecution-Decision-Child Criminal Justice System.